2020
DOI: 10.3389/fonc.2020.01037
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Autophagy and Wnt/β-Catenin Signaling in Cancer: Therapeutic Potential Through Drug Repositioning

Abstract: The widespread dysregulation that characterizes cancer cells has been dissected and many regulation pathways common to multiple cancer types have been described in depth. Wnt/β-catenin signaling and autophagy are among these principal pathways, which contribute to tumor growth and resistance to anticancer therapies. Currently, several therapeutic strategies that target either Wnt/β-catenin signaling or autophagy are in various stages of development. Targeted therapies that block specific elements that particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Besides that, a regulatory feedback between autophagy and Wnt/β-catenin signalling has been reported [ 51 ]. β-catenin negatively modulates autophagy by reducing autophagosome formation and LC3-II puncta during starvation and nutrient-rich conditions [ 52 ].…”
Section: Pathways Controlling Autophagymentioning
confidence: 99%
“…Besides that, a regulatory feedback between autophagy and Wnt/β-catenin signalling has been reported [ 51 ]. β-catenin negatively modulates autophagy by reducing autophagosome formation and LC3-II puncta during starvation and nutrient-rich conditions [ 52 ].…”
Section: Pathways Controlling Autophagymentioning
confidence: 99%
“…The Wnt signaling pathway is severely dysregulated in solid and non-solid malignant tumors, acting as part of the proliferation pathway that characterizes cancer cells [ 42 ]. Pérez-Plasencia et al reported that the Wnt signaling pathway, as a common pathway in many cancer types, was a main attractive target in cancer therapy [ 43 ], including HCC [ 35 ]. Dysregulation of the MAPK cascade is linked to some key signaling components and phosphorylation events which can activate the process of tumorigenesis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…is was also in line with the "double-edged" role of autophagy mentioned previously [21] which promoted the growth of tumor cells after tumorigenesis. Additionally, previous studies have revealed the close-knit relationship between autophagy and Wnt pathway in OS and other cancers [55,[58][59][60]. Tao et al reported that activation of Wnt pathway represses the expression of Beclin 1, a pivotal element for autophagic flux [61].…”
Section: Discussionmentioning
confidence: 99%
“…Integrating these results, we concluded that dysregulation of Wnt pathway may mediate the contrition of prognostic AGRs to the prognosis of OS patient. Wnt pathway was a crucial cascade involved in stemness and development, and aberrant Wnt pathway was usually implicated in tumorigenesis and progression [ 55 , 56 ]. It has been proved that there was a dual feedback regulation between Wnt pathway and autophagy [ 57 ], and GSVA analysis revealed that the negative regulation of autophagy was also hindered in the high-risk group in this study.…”
Section: Discussionmentioning
confidence: 99%